Experiência interdisciplinar através de projeto de trabalho no contexto da escola: saberes construídos pelos professores - Hammes, Care Cristiane (Universidade do Vale do Rio do Sinos, 2007)
The objective of this investigation was to understand the possibilities and limits of a pedagogical experience in an interdisciplinary perspective, accomplished through work projects, in the construction of teacher’s knowledge at a school scope. The experience was developed in the Instituto de Educação Ivoti/RS (Institute of Education of Ivoti/RS), where the collective work of production and application of the project “Missões Jesuíticas” took place, with participation of teachers and senior students from high school, in the first semester of 2006. In the investigation of this experience, my intention was to understand the role of the geographic knowledge linked to the knowledge of different disciplines of the curriculum and the possibilities of work projects that were accomplished in an interdisciplinary perspective, in the construction of teacher’s knowledge in the school environment and in the changes in their pedagogical practices. In the inquiry process, the e-mails exchanged among teachers in the planni
Keywords: geografia; projetos de trabalho; saberes docentes; interdisciplinar; geography; work projects; interdisciplinary; teacher’s knowledge; Ciências Humanas